Role of human milk in extremely low birth weight infants’ risk of necrotizing enterocolitis or death - Meinzen-Derr, J (2008)
OBJECTIVE: To determine the association between human milk (HM) intake and risk of necrotizing enterocolitis (NEC) or death among infants 401 to 1000 g birth weight. STUDY DESIGN: Analysis of 1272 infants in the National Institute of Child Health and Human Development Neonatal Network Glutamine Trial was performed to determine if increasing HM intake was associated with decreased risk of NEC or death. HM intake was defined as the proportion of HM to total intake, to enteral intake and total volume over the first 14 days. Known NEC risk factors were included as covariates in Cox proportional hazard analyses for duration of survival time free of NEC. RESULT: Among study infants, 13.6% died or developed NEC after 14 days. The likelihood of NEC or death after 14 days was decreased by a factor of 0.83 (95% confidence interval, CI 0.72, 0.96) for each 10% increase in the proportion of total intake as HM. Each 100 ml kg(–1) increase in HM intake during the first 14 days was associated with decreased risk of NEC or death (hazard ratio, HR 0.87 (95% CI 0.77, 0.97)). There appeared to be a trend towards a decreased risk of NEC or death among infants who received 100% HM as a proportion to total enteral intake (HM plus formula), although this finding was not statistically significant (HR 0.85 (95% CI 0.60, 1.19)). CONCLUSION: These data suggest a dose-related association of HM feeding with a reduction of risk of NEC or death after the first 2 weeks of life among extremely low birth weight infants.